2021
DOI: 10.1080/19390211.2021.1944947
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tinnitan Duo® in Subjective Tinnitus with Emotional Affectation: A Prospective, Interventional Study

Abstract: To assess the effectiveness of a food supplement (Tinnitan Duo V R ) containing 5-hydroxytryptophan, Ginkgo biloba, magnesium, melatonin, vitamin B5 and B6, and zinc at improving tinnitus response and intensity. Prospective, single-center interventional study including patients with subjective tinnitus and emotional affectation. The primary endpoint was the change in the Tinnitus Handicap Inventory (THI) total score and the emotional subscale after 3 months of treatment. Secondary endpoints were the change fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The results showed that values of total effectiveness of treatment in the research group after one course of treatment, and after three months of treatment, were significantly higher than those of the reference group. This is consistent with a previous finding which showed that after treatment, there were markedly improved THI scores in the research group and reference group, but with lower scores in the research group [13]. In this study, after treatment, the pure tone threshold and PSQ1 scores of the two groups of patients were significantly decreased, with lower outcomes in the research group than in the reference group.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that values of total effectiveness of treatment in the research group after one course of treatment, and after three months of treatment, were significantly higher than those of the reference group. This is consistent with a previous finding which showed that after treatment, there were markedly improved THI scores in the research group and reference group, but with lower scores in the research group [13]. In this study, after treatment, the pure tone threshold and PSQ1 scores of the two groups of patients were significantly decreased, with lower outcomes in the research group than in the reference group.…”
Section: Discussionsupporting
confidence: 92%
“…In concurrence, the study conducted by Kim, et al [ 11 ] depicted no significant change in SF-36 scores of patients treated with 160 mg of Ginkgo biloba . Likewise, Knäpper, et al [ 35 ] studied the effect of supplementation of Tinnitan Duo (food supplement, containing 5-hydroxy tryptophan, Ginkgo biloba , magnesium, zinc melatonin, vitamin B5 and B6) in patients with subjective tinnitus and emotional affectation for 3 months. The study resulted in improved emotional affectation and safety profile with no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…THI score was calculated on the basis of three subscales categorized as functional, emotional and catastrophic. Further, as per the grading system, determined by the British Association of Otolaryngologists, Head and Neck Surgeons, THI total score was interpreted and graded into varied levels: very mild (0-16), mild (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), moderate (38-56), severe (58-76), and catastrophic (78-100) [26]. The present study concluded Ginkgo biloba along with antioxidants was more effective in improving THI and VAS scores in patients as compared to Ginkgo Fig.…”
Section: Thi and Vas Scoresmentioning
confidence: 99%
“…Studies have looked into combining antioxidant vitamins A, C, E, selenium [ 63 ], and complex formulations including G. biloba along with magnesium, melatonin, vitamin B, and zinc. Significant improvements in tinnitus have been reported in some cases [ 64 ]. However, these are all single studies, and further research is needed to confirm their effectiveness.…”
Section: Reviewmentioning
confidence: 99%